The need to promote sleep health in public health agendas across the globe - Lim, Diane C; Najafi, Arezu; Afifi, Lamia; Bassetti, Claudio LA; Buysse, Daniel J; Han, Fang; Högl, Birgit; Melaku, Yohannes Adama; Morin, Charles M; Pack, Allan I; Poyares, Dalva; Somers, Virend K; et al. (The Lancet. Public health, 2023)
Healthy sleep is essential for physical and mental health, and social wellbeing; however, across the globe, and particularly in developing countries, national public health agendas rarely consider sleep health. Sleep should be promoted as an essential pillar of health, equivalent to nutrition and physical activity. To improve sleep health across the globe, a focus on education and awareness, research, and targeted public health policies are needed. We recommend developing sleep health educational programmes and awareness campaigns; increasing, standardising, and centralising data on sleep quantity and quality in every country across the globe; and developing and implementing sleep health policies across sectors of society. Efforts are needed to ensure equity and inclusivity for all people, particularly those who are most socially and economically vulnerable, and historically excluded.